Pengaruh Literasi Keuangan dan Lifestyle Terhadap Pengelolaan Keuangan Pribadi Gen-Z pada Mahasiswa IAIN Palopo - Nurul Husna S; Hapid; Samsul Bachri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
In today's modern era, many people, especially the younger generation, face difficulties in managing their personal finances, which is often caused by low financial literacy and a lifestyle that is not in accordance with financial conditions. This study aims to determine the effect of financial literacy and lifestyle on Gen-Z personal financial management in IAIN Palopo students. the method used in this study uses quantitative methods with multiple linear regression techniques, with a sample size of 75 respondents, namely IAIN Palopo students in the Sharia Economics study program class of 2021, 2022, and 2023. Data collection was carried out using a questionnaire consisting of three variables, namely financial literacy, lifestyle, and personal financial management. The results of this study indicate that financial literacy has a positive and significant effect on student personal financial management, lifestyle has a positive and significant effect on student personal financial management, and simultaneously financial literacy and lifestyle have a positive and sign ificant effect on personal financial management in Gen-Z students of IAIN Palopo.